Cons of AI in higher education - Kechil, Rafizah; Mohd Mydin, Azlina (Unit Penerbitan Dan Publisiti JSKM, 2025)
As the integration of artificial intelligence (AI) deepens within higher education, it is crucial to address the potential drawbacks and challenges associated with its implementation. While AI offers numerous benefits, the following cons reflect critical areas of concern that both educators and students must consider. Data Privacy Concerns One of the most significant issues surrounding AI in higher education involves data privacy. The sensitive nature of student data necessitates stringent measures to safeguard personal information. Key concerns include: Data Collection: AI systems rely heavily on data analytics, which can entail the collection of vast amounts of student information, including academic performance, personal preferences, and interaction patterns. A report by the Educause Center for Analysis and Research highlighted that 85% of higher education leaders expressed concerns over unsanctioned data usage.